Atypical endodontic access and coronary reconstruction in anterior teeth: case report (Research, Society and Development, 2022)
The use of conservative techniques in dentistry contributes to the preservation of tooth structure. This article aims to provide a less invasive dental treatment, preserving the integrity of the dental structure with satisfactory results. The reference and database information were obtained from scientific articles published in Google academic, Scielo and PubMed, based on the presented topic and using a combination of keywords. In this case, dental treatment was performed on teeth with multiple carious lesions and coronary destruction, the proposed treatment plan was endodontic treatment with atypical access (on the buccal surface), coronary reconstruction using a fiberglass post, associated with composite resin. which presents a good aesthetic result. Finally, the treatment must achieve an aesthetic and functional result, without high cost and, in addition, it can meet the patient's needs, returning self-esteem and a beautiful and harmonious smile.